Unlock creative energy, generate new ideas, brainstorm effectively. (Boston, 2015)
Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives—from the most trusted source in business. Also available as an ebook. It shows you how to:Create the right environment for inventive thinking, Build a diverse team, Generate a wide array of new ideas,Manage disagreements,Make sure your ideas actually get implemented
Keywords: Khả năng sáng tạo trong kinh doanh,Suy nghĩ sáng tạo,Sản phẩm mới,Tổ tại nơi làm việc,Creative thinking,New products,Teams in the workplace,Creative ability in business; Sự quản lý,Management